High-strength wear-resistant conveyor belt and preparation method thereof

CN122978484APending Publication Date: 2026-10-27NINGSHUN GROUP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611283765.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]现有输送带还存在许多技术问题,例如:输送带的浸胶层与纤维表面主要依靠物理吸附和机械咬合结合,在高负载的运作下粘合力下降,易发生层间脱层

Benefits of technology

[0022]1、本发明制备的输送带以聚丙烯为基体,丁腈橡胶为分散相,马来酸酐接枝聚丙烯的酸酐基与炭黑表面羟基、玻璃纤维表面稀土离子及氨基硅烷反应。使得聚丙烯、丁腈橡胶相界面结合强度提高,从而提高输送带的力学性能。浆料中添加的马来酸酐接枝聚丙烯与混炼胶中的聚丙烯反应,酸酐基团与氨基硅烷的氨基反应,环氧化天然橡胶的环氧基与氨基硅烷反应,与橡胶共硫化,使得输送带的力学性能提高。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a high-strength wear-resistant conveying belt and a preparation method thereof, and relates to the technical field of conveying belts.The conveying belt is prepared from polypropylene as a base, nitrile rubber as a dispersed phase, and anhydride groups of maleic anhydride grafted polypropylene reacting with hydroxyl groups on the surface of carbon black, rare earth ions on the surface of glass fibers and amino silane, so that the interfacial bonding strength of the polypropylene and the nitrile rubber is improved, and the mechanical properties of the conveying belt are improved.The maleic anhydride grafted polypropylene in the slurry reacts with the polypropylene in the mixing rubber, the anhydride groups react with the amino groups of the amino silane, the epoxy groups of the epoxidized natural rubber react with the amino silane, and the rubber is co-vulcanized, so that the mechanical properties of the conveying belt are improved.The addition of cerium dioxide modified calcium silicate further improves the strength and wear resistance of the conveying belt.The belt core is treated by plasma and silane coupling agent, and the interfacial adhesion between the belt core and the rubber is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of conveyor belt technology, specifically a high-strength wear-resistant conveyor belt and its preparation method. Background Technology

[0002] Conveyor belts are widely used in industries such as mining, metallurgy, and ports. With the increase in conveying capacity and operating speed, there are increasingly higher requirements for the tensile strength, wear resistance, and interlayer adhesion strength of conveyor belts.

[0003] Existing conveyor belts still have many technical problems. For example, the adhesive layer of the conveyor belt mainly relies on physical adsorption and mechanical interlocking to bond with the fiber surface. Under high load operation, the adhesion decreases, and interlayer delamination is prone to occur. It is difficult to balance the wear resistance and strength of the cover rubber. When the conveyor belt is transporting materials, the surface of the cover rubber is easily worn. To improve wear resistance, existing technologies usually increase the amount of carbon black, but high filler will lead to high rubber viscosity and reduced tear resistance.

[0004] To address the aforementioned problems and improve the strength and wear resistance of conveyor belts, this application provides a high-strength wear-resistant conveyor belt and its preparation method. Summary of the Invention

[0005] The purpose of this invention is to provide a high-strength wear-resistant conveyor belt and its preparation method, so as to solve the problems raised in the prior art.

[0006] To achieve the above objectives, the present invention provides the following technical solution:

[0007] A method for preparing a high-strength, wear-resistant conveyor belt includes the following steps:

[0008] S1: Mix rare earth coupling agent and liquid paraffin evenly to obtain a modifier; spray the modifier evenly onto glass fiber, stir and dry to obtain rare earth modified glass fiber; then immerse the rare earth modified glass fiber in epoxidized rubber latex, take it out and dry to obtain modified glass fiber.

[0009] S2: Take polypropylene, nitrile rubber, epoxidized rubber latex, maleic anhydride-grafted polypropylene, carbon black, silica, bis-[3-(triethoxysilyl)propyl]tetrasulfide, cerium dioxide-modified calcium silicate, modified glass fiber, zinc oxide, stearic acid, N-isopropyl-N'-phenyl-p-phenylenediamine, paraffin wax, and N-cyclohexyl-2-benzothiazole sulfenamide, mix them, add sulfur, mix again, pass through a thin sheet, and extrude to obtain the compound rubber.

[0010] S3: The compounded rubber is calendered and bonded to the top and bottom of the belt core, and then vulcanized to obtain a high-strength wear-resistant conveyor belt.

[0011] A more optimized method for preparing the core includes the following steps:

[0012] Step 1: Take maleic anhydride-grafted polypropylene, epoxidized rubber latex, nitrile rubber, carbon black, phenolic resin, zinc oxide, stearic acid, sulfur, and N-cyclohexyl-2-benzothiazole sulfenamide, stir evenly to obtain a slurry;

[0013] Step 2: The core is subjected to plasma treatment, and then impregnated with a silane coupling agent to obtain a pretreated core;

[0014] Step 3: Coat both sides of the pretreated core with slurry and dry to obtain the core.

[0015] More preferably, the silane coupling agent is a mixture of 3-mercaptopropyltrimethoxysilane and 3-aminopropyltriethoxysilane.

[0016] Ideally, the mass ratio of 3-mercaptopropyltrimethoxysilane to 3-aminopropyltriethoxysilane is 1:(2-2.5).

[0017] In a more optimized manner, in step two, the core is subjected to vacuum plasma treatment by introducing a mixture of oxygen and argon gas for 90-100 seconds to obtain the plasma-treated core.

[0018] In a more optimized manner, the operation method for impregnation treatment using silane coupling agent in step two is as follows: take deionized water and ethanol, add glacial acetic acid to adjust the pH value to 4.5-5 to obtain a solvent, add 3-mercaptopropyltrimethoxysilane and 3-aminopropyltriethoxysilane, stir for 30-40 min to obtain an impregnation solution; immerse the plasma-treated core in the impregnation solution for 20-30 min, and dry to obtain the pretreated core.

[0019] A more optimized method for preparing cerium dioxide-modified calcium silicate is as follows: calcium silicate and ethanol are taken, dispersed evenly, cerium nitrate hexahydrate is added, stirred for 30-40 min, reacted at 160-165℃ for 12-14 h, filtered, washed, and dried to obtain cerium dioxide-modified calcium silicate.

[0020] More preferably, the compound comprises the following components, calculated by weight parts: 45-50 parts polypropylene, 35-40 parts nitrile rubber, 8-12 parts epoxidized rubber latex, 7-10 parts maleic anhydride-grafted polypropylene, 30-36 parts carbon black, 12-20 parts silica, 1-2 parts bis-[3-(triethoxysilyl)propyl]tetrasulfide, 7-9 parts cerium dioxide-modified calcium silicate, 8-9 parts modified glass fiber, 4-6 parts zinc oxide, 2-3 parts stearic acid, 2-3 parts N-isopropyl-N'-phenyl-p-phenylenediamine, 1-2 parts paraffin wax, 1.5-2 parts sulfur, and 1.5-2 parts N-cyclohexyl-2-benzothiazole sulfenamide.

[0021] Compared with the prior art, the beneficial effects of the present invention are:

[0022] 1. The conveyor belt prepared by this invention uses polypropylene as the matrix and nitrile rubber as the dispersed phase. The anhydride groups of maleic anhydride-grafted polypropylene react with the hydroxyl groups on the carbon black surface, rare earth ions on the glass fiber surface, and aminosilanes. This improves the interfacial bonding strength between the polypropylene and nitrile rubber phases, thereby enhancing the mechanical properties of the conveyor belt. The maleic anhydride-grafted polypropylene added to the slurry reacts with the polypropylene in the compound, the anhydride groups react with the amino groups of the aminosilanes, and the epoxy groups of the epoxidized natural rubber react with the aminosilanes, co-curing with the rubber, further improving the mechanical properties of the conveyor belt.

[0023] 2. The addition of cerium dioxide-modified calcium silicate further improves the strength and wear resistance of the conveyor belt. Rare earth ions form coordination bonds with the silicon-oxygen bonds on the surface of glass fibers, and then an epoxy rubber layer is coated on the surface of the glass fibers. The epoxy groups of the epoxy rubber can form hydrogen bonds with the surface of the glass fibers, and can also be co-vulcanized with the rubber to improve the strength of the rubber.

[0024] 3. The core is treated with plasma and a silane coupling agent. The ethoxy and methoxy groups of the silane condense with the hydroxyl groups on the surface of the aramid fiber core to form siloxane bonds. The amino group of 3-aminopropyltriethoxysilane forms an imide bond with the anhydride of maleic anhydride-grafted polypropylene and undergoes a ring-opening reaction with the epoxy groups of epoxidized natural rubber. The mercapto groups of 3-mercaptopropyltrimethoxysilane crosslink with the rubber. This improves the interfacial adhesion between the core and the rubber. Detailed Implementation

[0025] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0026] The sources and types of substances involved in this application are not specifically limited. Examples include: polypropylene: melt index 2.2 g / 10 min; rare earth coupling agent: rare earth metal Re content 3.5-6.5 wt%.

[0027] Glass fiber: diameter 6-12μm, length 3-5mm; Phenolic resin: resorcinol formaldehyde resin, solid content: 40-50%.

[0028] Example 1: A method for preparing a high-strength wear-resistant conveyor belt, comprising the following steps:

[0029] Step 1:

[0030] Take polypropylene, nitrile rubber, epoxidized rubber latex, maleic anhydride-grafted polypropylene, carbon black, silica, bis-[3-(triethoxysilyl)propyl]tetrasulfide, cerium dioxide-modified calcium silicate, modified glass fiber, zinc oxide, stearic acid, N-isopropyl-N'-phenyl-p-phenylenediamine, paraffin wax, and N-cyclohexyl-2-benzothiazole sulfenamide, mix them, add sulfur, mix again, pass through a thin sheet, and extrude to obtain the compound rubber.

[0031] The compounded rubber is calendered and bonded to the top and bottom of the belt core, and then vulcanized to obtain a high-strength and wear-resistant conveyor belt.

[0032] 47 parts polypropylene, 38 parts nitrile rubber, 10 parts epoxidized rubber latex, 8 parts maleic anhydride-grafted polypropylene, 32 parts carbon black, 15 parts silica, 1.5 parts bis-[3-(triethoxysilyl)propyl]tetrasulfide, 8 parts cerium dioxide-modified calcium silicate, 8 parts modified glass fiber, 5 parts zinc oxide, 2.5 parts stearic acid, 2.5 parts N-isopropyl-N'-phenyl-p-phenylenediamine, 1 part paraffin wax, 1.5 parts sulfur, 1.5 parts N-cyclohexyl-2-benzothiazole sulfenamide;

[0033] Step 2: Preparation of cerium dioxide modified calcium silicate:

[0034] Take 30g of calcium silicate and 500mL of ethanol, disperse them evenly, add 1g of cerium nitrate hexahydrate, stir for 35min, react at 162℃ for 13h, filter, wash and dry to obtain cerium dioxide modified calcium silicate;

[0035] Step 3: Preparation of modified glass fiber:

[0036] 1g of rare earth coupling agent and 1g of liquid paraffin were stirred evenly to obtain a modifier; the modifier was evenly sprayed onto 100g of glass fiber, stirred and dried to obtain rare earth modified glass fiber; then the rare earth modified glass fiber was immersed in epoxidized rubber latex with a solid content of 12% and an epoxy degree of 25mol% for 6 minutes, removed and dried to obtain modified glass fiber;

[0037] Step 4: Core Preparation

[0038] Plasma-treated belt core: The aramid fiber cloth belt core is subjected to vacuum plasma treatment by introducing a mixture of oxygen and argon gas with a volume ratio of 4:1 and treatment for 95 seconds to obtain the plasma-treated belt core.

[0039] Take 40 mL of deionized water and 160 mL of ethanol, add glacial acetic acid to adjust the pH to 4.5 to obtain a solvent, add 1 g of 3-mercaptopropyltrimethoxysilane and 2.2 g of 3-aminopropyltriethoxysilane, stir for 35 min to obtain an impregnation solution;

[0040] The plasma-treated core was immersed in an impregnation solution for 25 minutes and then dried to obtain the pretreated core.

[0041] Step 5: Slurry preparation:

[0042] Take 25 parts by weight of maleic anhydride-grafted polypropylene, 27 parts by weight of epoxidized rubber latex, 36 parts by weight of nitrile rubber, 15 parts by weight of carbon black, 5 parts by weight of phenolic resin, 5 parts by weight of zinc oxide, 1 part by weight of stearic acid, 2.5 parts by weight of sulfur, and 1 part by weight of N-cyclohexyl-2-benzothiazole sulfenamide, stir evenly to obtain a slurry.

[0043] The slurry was coated on both sides of the pretreated belt core, with a single-sided coating amount of 25 g / m. 2 Drying yields the core.

[0044] Example 2: A method for preparing a high-strength wear-resistant conveyor belt, comprising the following steps:

[0045] Step 1:

[0046] Take polypropylene, nitrile rubber, epoxidized rubber latex, maleic anhydride-grafted polypropylene, carbon black, silica, bis-[3-(triethoxysilyl)propyl]tetrasulfide, cerium dioxide-modified calcium silicate, modified glass fiber, zinc oxide, stearic acid, N-isopropyl-N'-phenyl-p-phenylenediamine, paraffin wax, and N-cyclohexyl-2-benzothiazole sulfenamide, mix them, add sulfur, mix again, pass through a thin sheet, and extrude to obtain the compound rubber.

[0047] The compounded rubber is calendered and bonded to the top and bottom of the belt core, and then vulcanized to obtain a high-strength and wear-resistant conveyor belt.

[0048] 45 parts polypropylene, 35 parts nitrile rubber, 8 parts epoxidized rubber latex, 7 parts maleic anhydride-grafted polypropylene, 30 parts carbon black, 12 parts silica, 1 part bis-[3-(triethoxysilyl)propyl]tetrasulfide, 7 parts cerium dioxide-modified calcium silicate, 8 parts modified glass fiber, 4 parts zinc oxide, 2 parts stearic acid, 2 parts N-isopropyl-N'-phenyl-p-phenylenediamine, 1 part paraffin wax, 1.5 parts sulfur, 1.5 parts N-cyclohexyl-2-benzothiazole sulfenamide;

[0049] Step 2: Preparation of cerium dioxide modified calcium silicate:

[0050] Take 30g of calcium silicate and 500mL of ethanol, disperse them evenly, add 1g of cerium nitrate hexahydrate, stir for 30min, react at 160℃ for 12h, filter, wash and dry to obtain cerium dioxide modified calcium silicate;

[0051] Step 3: Preparation of modified glass fiber:

[0052] 1g of rare earth coupling agent and 1g of liquid paraffin were stirred evenly to obtain a modifier; the modifier was evenly sprayed onto 100g of glass fiber, stirred and dried to obtain rare earth modified glass fiber; then the rare earth modified glass fiber was immersed in epoxidized rubber latex with a solid content of 12% and an epoxy degree of 25mol% for 5 minutes, removed and dried to obtain modified glass fiber;

[0053] Step 4: Core Preparation

[0054] Plasma-treated belt core: The aramid fiber cloth belt core is subjected to vacuum plasma treatment by introducing a mixture of oxygen and argon gas with a volume ratio of 4:1 and treatment for 90 seconds to obtain the plasma-treated belt core.

[0055] Take 40 mL of deionized water and 160 mL of ethanol, add glacial acetic acid to adjust the pH to 4.5 to obtain a solvent, add 1 g of 3-mercaptopropyltrimethoxysilane and 2.2 g of 3-aminopropyltriethoxysilane, stir for 30 min to obtain an impregnation solution;

[0056] The plasma-treated core was immersed in an impregnation solution for 20 minutes and then dried to obtain the pretreated core.

[0057] Step 5: Slurry preparation:

[0058] Take 25 parts by weight of maleic anhydride-grafted polypropylene, 27 parts by weight of epoxidized rubber latex, 36 parts by weight of nitrile rubber, 15 parts by weight of carbon black, 5 parts by weight of phenolic resin, 5 parts by weight of zinc oxide, 1 part by weight of stearic acid, 2.5 parts by weight of sulfur, and 1 part by weight of N-cyclohexyl-2-benzothiazole sulfenamide, stir evenly to obtain a slurry.

[0059] The slurry was coated on both sides of the pretreated belt core, with a single-sided coating amount of 25 g / m. 2 Drying yields the core.

[0060] Example 3: A method for preparing a high-strength wear-resistant conveyor belt, comprising the following steps:

[0061] Step 1:

[0062] Take polypropylene, nitrile rubber, epoxidized rubber latex, maleic anhydride-grafted polypropylene, carbon black, silica, bis-[3-(triethoxysilyl)propyl]tetrasulfide, cerium dioxide-modified calcium silicate, modified glass fiber, zinc oxide, stearic acid, N-isopropyl-N'-phenyl-p-phenylenediamine, paraffin wax, and N-cyclohexyl-2-benzothiazole sulfenamide, mix them, add sulfur, mix again, pass through a thin sheet, and extrude to obtain the compound rubber.

[0063] The compounded rubber is calendered and bonded to the top and bottom of the belt core, and then vulcanized to obtain a high-strength and wear-resistant conveyor belt.

[0064] 50 parts polypropylene, 40 parts nitrile rubber, 12 parts epoxidized rubber latex, 10 parts maleic anhydride-grafted polypropylene, 36 parts carbon black, 20 parts silica, 2 parts bis-[3-(triethoxysilyl)propyl]tetrasulfide, 9 parts cerium dioxide-modified calcium silicate, 8 parts modified glass fiber, 6 parts zinc oxide, 3 parts stearic acid, 3 parts N-isopropyl-N'-phenyl-p-phenylenediamine, 2 parts paraffin wax, 2 parts sulfur, 2 parts N-cyclohexyl-2-benzothiazole sulfenamide;

[0065] Step 2: Preparation of cerium dioxide modified calcium silicate:

[0066] Take 30g of calcium silicate and 500mL of ethanol, disperse them evenly, add 1g of cerium nitrate hexahydrate, stir for 40min, react at 165℃ for 14h, filter, wash and dry to obtain cerium dioxide modified calcium silicate;

[0067] Step 3: Preparation of modified glass fiber:

[0068] 1g of rare earth coupling agent and 1g of liquid paraffin were stirred evenly to obtain a modifier; the modifier was evenly sprayed onto 100g of glass fiber, stirred and dried to obtain rare earth modified glass fiber; then the rare earth modified glass fiber was immersed in epoxidized rubber latex with a solid content of 12% and an epoxy degree of 25mol% for 7 minutes, removed and dried to obtain modified glass fiber;

[0069] Step 4: Core Preparation

[0070] Plasma-treated belt core: The aramid fiber cloth belt core is subjected to vacuum plasma treatment by introducing a mixture of oxygen and argon gas with a volume ratio of 4:1 and treatment for 100 seconds to obtain the plasma-treated belt core.

[0071] Take 40 mL of deionized water and 160 mL of ethanol, add glacial acetic acid to adjust the pH to 4.5 to obtain a solvent, add 1 g of 3-mercaptopropyltrimethoxysilane and 2.2 g of 3-aminopropyltriethoxysilane, stir for 40 min to obtain an impregnation solution;

[0072] The plasma-treated core was immersed in an impregnation solution for 30 minutes and then dried to obtain the pretreated core.

[0073] Step 5: Slurry preparation:

[0074] Take 25 parts by weight of maleic anhydride-grafted polypropylene, 27 parts by weight of epoxidized rubber latex, 36 parts by weight of nitrile rubber, 15 parts by weight of carbon black, 5 parts by weight of phenolic resin, 5 parts by weight of zinc oxide, 1 part by weight of stearic acid, 2.5 parts by weight of sulfur, and 1 part by weight of N-cyclohexyl-2-benzothiazole sulfenamide, stir evenly to obtain a slurry.

[0075] The slurry was coated on both sides of the pretreated belt core, with a single-sided coating amount of 25 g / m. 2 Drying yields the core.

[0076] Comparative Example 1: No cerium dioxide modification was performed on calcium silicate; all other aspects were the same as in Example 1.

[0077] Step 1:

[0078] Take polypropylene, nitrile rubber, epoxidized rubber latex, maleic anhydride-grafted polypropylene, carbon black, silica, bis-[3-(triethoxysilyl)propyl]tetrasulfide, calcium silicate, modified glass fiber, zinc oxide, stearic acid, N-isopropyl-N'-phenyl-p-phenylenediamine, paraffin wax, and N-cyclohexyl-2-benzothiazole sulfenamide, mix them, add sulfur, mix again, pass through a thin sheet, and extrude to obtain the compound rubber.

[0079] The compounded rubber is calendered and bonded to the top and bottom of the belt core, and then vulcanized to obtain a high-strength and wear-resistant conveyor belt.

[0080] 47 parts polypropylene, 38 parts nitrile rubber, 10 parts epoxidized rubber latex, 8 parts maleic anhydride grafted polypropylene, 32 parts carbon black, 15 parts silica, 1.5 parts bis-[3-(triethoxysilyl)propyl]tetrasulfide, 8 parts calcium silicate, 8 parts modified glass fiber, 5 parts zinc oxide, 2.5 parts stearic acid, 2.5 parts N-isopropyl-N'-phenyl-p-phenylenediamine, 1 part paraffin wax, 1.5 parts sulfur, 1.5 parts N-cyclohexyl-2-benzothiazole sulfenamide;

[0081] Step 2: Preparation of modified glass fiber:

[0082] 1g of rare earth coupling agent and 1g of liquid paraffin were stirred evenly to obtain a modifier; the modifier was evenly sprayed onto 100g of glass fiber, stirred and dried to obtain rare earth modified glass fiber; then the rare earth modified glass fiber was immersed in epoxidized rubber latex with a solid content of 12% and an epoxy degree of 25mol% for 6 minutes, removed and dried to obtain modified glass fiber;

[0083] Step 3: Core preparation:

[0084] Plasma-treated belt core: The aramid fiber cloth belt core is subjected to vacuum plasma treatment by introducing a mixture of oxygen and argon gas with a volume ratio of 4:1 and treatment for 95 seconds to obtain the plasma-treated belt core.

[0085] Take 40 mL of deionized water and 160 mL of ethanol, add glacial acetic acid to adjust the pH to 4.5 to obtain a solvent, add 1 g of 3-mercaptopropyltrimethoxysilane and 2.2 g of 3-aminopropyltriethoxysilane, stir for 35 min to obtain an impregnation solution;

[0086] The plasma-treated core was immersed in an impregnation solution for 25 minutes and then dried to obtain the pretreated core.

[0087] Step 4: Slurry preparation:

[0088] Take 25 parts by weight of maleic anhydride-grafted polypropylene, 27 parts by weight of epoxidized rubber latex, 36 parts by weight of nitrile rubber, 15 parts by weight of carbon black, 5 parts by weight of phenolic resin, 5 parts by weight of zinc oxide, 1 part by weight of stearic acid, 2.5 parts by weight of sulfur, and 1 part by weight of N-cyclohexyl-2-benzothiazole sulfenamide, stir evenly to obtain a slurry.

[0089] The slurry was coated on both sides of the pretreated belt core, with a single-sided coating amount of 25 g / m. 2 Drying yields the core.

[0090] Comparative Example 2: No epoxidized rubber latex modification was performed on the glass fiber; all other aspects were the same as in Example 1.

[0091] Step 1:

[0092] Take polypropylene, nitrile rubber, epoxidized rubber latex, maleic anhydride-grafted polypropylene, carbon black, silica, bis-[3-(triethoxysilyl)propyl]tetrasulfide, cerium dioxide-modified calcium silicate, modified glass fiber, zinc oxide, stearic acid, N-isopropyl-N'-phenyl-p-phenylenediamine, paraffin wax, and N-cyclohexyl-2-benzothiazole sulfenamide, mix them, add sulfur, mix again, pass through a thin sheet, and extrude to obtain the compound rubber.

[0093] The compounded rubber is calendered and bonded to the top and bottom of the belt core, and then vulcanized to obtain a high-strength and wear-resistant conveyor belt.

[0094] 47 parts polypropylene, 38 parts nitrile rubber, 10 parts epoxidized rubber latex, 8 parts maleic anhydride-grafted polypropylene, 32 parts carbon black, 15 parts silica, 1.5 parts bis-[3-(triethoxysilyl)propyl]tetrasulfide, 8 parts cerium dioxide-modified calcium silicate, 8 parts modified glass fiber, 5 parts zinc oxide, 2.5 parts stearic acid, 2.5 parts N-isopropyl-N'-phenyl-p-phenylenediamine, 1 part paraffin wax, 1.5 parts sulfur, 1.5 parts N-cyclohexyl-2-benzothiazole sulfenamide;

[0095] Step 2: Preparation of cerium dioxide modified calcium silicate:

[0096] Take 30g of calcium silicate and 500mL of ethanol, disperse them evenly, add 1g of cerium nitrate hexahydrate, stir for 35min, react at 162℃ for 13h, filter, wash and dry to obtain cerium dioxide modified calcium silicate;

[0097] Step 3: Preparation of modified glass fiber:

[0098] 1g of rare earth coupling agent and 1g of liquid paraffin are stirred evenly to obtain a modifier; the modifier is evenly sprayed onto 100g of glass fiber, stirred and dried to obtain modified glass fiber;

[0099] Step 4: Core Preparation

[0100] Plasma-treated belt core: The aramid fiber cloth belt core is subjected to vacuum plasma treatment by introducing a mixture of oxygen and argon gas with a volume ratio of 4:1 and treatment for 95 seconds to obtain the plasma-treated belt core.

[0101] Take 40 mL of deionized water and 160 mL of ethanol, add glacial acetic acid to adjust the pH to 4.5 to obtain a solvent, add 1 g of 3-mercaptopropyltrimethoxysilane and 2.2 g of 3-aminopropyltriethoxysilane, stir for 35 min to obtain an impregnation solution;

[0102] The plasma-treated core was immersed in an impregnation solution for 25 minutes and then dried to obtain the pretreated core.

[0103] Step 5: Slurry preparation:

[0104] Take 25 parts by weight of maleic anhydride-grafted polypropylene, 27 parts by weight of epoxidized rubber latex, 36 parts by weight of nitrile rubber, 15 parts by weight of carbon black, 5 parts by weight of phenolic resin, 5 parts by weight of zinc oxide, 1 part by weight of stearic acid, 2.5 parts by weight of sulfur, and 1 part by weight of N-cyclohexyl-2-benzothiazole sulfenamide, stir evenly to obtain a slurry.

[0105] The slurry was coated on both sides of the pretreated belt core, with a single-sided coating amount of 25 g / m. 2 Drying yields the core.

[0106] Comparative Example 3: Without the addition of 3-mercaptopropyltrimethoxysilane, the rest was the same as in Example 1:

[0107] Step 1:

[0108] Take polypropylene, nitrile rubber, epoxidized rubber latex, maleic anhydride-grafted polypropylene, carbon black, silica, bis-[3-(triethoxysilyl)propyl]tetrasulfide, cerium dioxide-modified calcium silicate, modified glass fiber, zinc oxide, stearic acid, N-isopropyl-N'-phenyl-p-phenylenediamine, paraffin wax, and N-cyclohexyl-2-benzothiazole sulfenamide, mix them, add sulfur, mix again, pass through a thin sheet, and extrude to obtain the compound rubber.

[0109] The compounded rubber is calendered and bonded to the top and bottom of the belt core, and then vulcanized to obtain a high-strength and wear-resistant conveyor belt.

[0110] 47 parts polypropylene, 38 parts nitrile rubber, 10 parts epoxidized rubber latex, 8 parts maleic anhydride-grafted polypropylene, 32 parts carbon black, 15 parts silica, 1.5 parts bis-[3-(triethoxysilyl)propyl]tetrasulfide, 8 parts cerium dioxide-modified calcium silicate, 8 parts modified glass fiber, 5 parts zinc oxide, 2.5 parts stearic acid, 2.5 parts N-isopropyl-N'-phenyl-p-phenylenediamine, 1 part paraffin wax, 1.5 parts sulfur, 1.5 parts N-cyclohexyl-2-benzothiazole sulfenamide;

[0111] Step 2: Preparation of cerium dioxide modified calcium silicate:

[0112] Take 30g of calcium silicate and 500mL of ethanol, disperse them evenly, add 1g of cerium nitrate hexahydrate, stir for 35min, react at 162℃ for 13h, filter, wash and dry to obtain cerium dioxide modified calcium silicate;

[0113] Step 3: Preparation of modified glass fiber:

[0114] 1g of rare earth coupling agent and 1g of liquid paraffin were stirred evenly to obtain a modifier; the modifier was evenly sprayed onto 100g of glass fiber, stirred and dried to obtain rare earth modified glass fiber; then the rare earth modified glass fiber was immersed in epoxidized rubber latex with a solid content of 12% and an epoxy degree of 25mol% for 6 minutes, removed and dried to obtain modified glass fiber;

[0115] Step 4: Core Preparation

[0116] Plasma-treated belt core: The aramid fiber cloth belt core is subjected to vacuum plasma treatment by introducing a mixture of oxygen and argon gas with a volume ratio of 4:1 and treatment for 95 seconds to obtain the plasma-treated belt core.

[0117] Take 40 mL of deionized water and 160 mL of ethanol, add glacial acetic acid to adjust the pH to 4.5 to obtain a solvent, add 3.2 g of 3-aminopropyltriethoxysilane, stir for 35 min to obtain an impregnation solution;

[0118] The plasma-treated core was immersed in an impregnation solution for 25 minutes and then dried to obtain the pretreated core.

[0119] Step 5: Slurry preparation:

[0120] Take 25 parts by weight of maleic anhydride-grafted polypropylene, 27 parts by weight of epoxidized rubber latex, 36 parts by weight of nitrile rubber, 15 parts by weight of carbon black, 5 parts by weight of phenolic resin, 5 parts by weight of zinc oxide, 1 part by weight of stearic acid, 2.5 parts by weight of sulfur, and 1 part by weight of N-cyclohexyl-2-benzothiazole sulfenamide, stir evenly to obtain a slurry.

[0121] The slurry was coated on both sides of the pretreated belt core, with a single-sided coating amount of 25 g / m. 2 Drying yields the core.

[0122] experiment:

[0123] The conveyor belts prepared in Examples 1-3 and Comparative Examples 1-3 were subjected to performance tests. Referring to GB / T 528-2009, the compound rubber prepared according to this invention was used as a sample. The sample dimensions were: length 120 mm, end width 25 mm, narrow portion width 6 mm, narrow portion length 35 mm, and thickness 2 mm, characterizing its tensile strength. The conveyor belts were cut into strip-shaped samples of 200×200 mm, aged at 175℃ for 1 hour, and then removed. The adhesion strength between the upper and lower bonded compound rubber and the belt core was tested, characterizing its bonding force. Referring to GB / T1689-2014, the samples were fixed on the rubber wheel shaft, pre-ground for 20 minutes, and weighed (m1). After traveling 1.6 km, the weight (m2) was measured, and the wear volume was calculated, characterizing its wear resistance. The results are shown in Table 1 below.

[0124] Table 1

[0125]

[0126] Conclusions: In Comparative Example 1, the strength and wear resistance of the conveyor belt decreased due to the absence of cerium dioxide modification on calcium silicate. In Comparative Example 2, the strength and wear resistance of the conveyor belt decreased due to the absence of epoxidized rubber latex modification on glass fibers. In the examples, the epoxy groups of the epoxidized rubber can form hydrogen bonds with the surface of glass fibers and can also be co-vulcanized with rubber, thereby improving the strength and wear resistance of rubber. In Comparative Example 3, without the addition of 3-mercaptopropyltrimethoxysilane and using only one coupling agent, the adhesion strength between the belt core and the rubber decreased. In the examples, the belt core was treated with plasma and a silane coupling agent. The ethoxy and methoxy groups of the silane condensed with the hydroxyl groups on the surface of the aramid fiber belt core to form siloxane bonds. The amino group of 3-aminopropyltriethoxysilane formed an imide bond with the anhydride grafted onto maleic anhydride of polypropylene and underwent a ring-opening reaction with the epoxy groups of the epoxidized natural rubber.

[0127] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from the spirit or essential characteristics of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, it is intended that all variations falling within the meaning and scope of equivalents of the claims be included within the present invention.

Claims

1. A method for preparing a high-strength, wear-resistant conveyor belt, characterized in that: Includes the following steps: S1: Mix rare earth coupling agent and liquid paraffin evenly to obtain a modifier; spray the modifier evenly onto glass fiber, stir and dry to obtain rare earth modified glass fiber; then immerse the rare earth modified glass fiber in epoxidized rubber latex, take it out and dry to obtain modified glass fiber. S2: Take polypropylene, nitrile rubber, epoxidized rubber latex, maleic anhydride-grafted polypropylene, carbon black, silica, bis-[3-(triethoxysilyl)propyl]tetrasulfide, cerium dioxide-modified calcium silicate, modified glass fiber, zinc oxide, stearic acid, N-isopropyl-N'-phenyl-p-phenylenediamine, paraffin wax, and N-cyclohexyl-2-benzothiazole sulfenamide, mix them, add sulfur, mix again, pass through a thin sheet, and extrude to obtain the compound rubber. S3: The compounded rubber is calendered and bonded to the top and bottom of the belt core, and then vulcanized to obtain a high-strength wear-resistant conveyor belt.

2. The method for preparing a high-strength wear-resistant conveyor belt according to claim 1, characterized in that: The method for preparing the core includes the following steps: Step 1: Take maleic anhydride-grafted polypropylene, epoxidized rubber latex, nitrile rubber, carbon black, phenolic resin, zinc oxide, stearic acid, sulfur, and N-cyclohexyl-2-benzothiazole sulfenamide, stir evenly to obtain a slurry; Step 2: The core is subjected to plasma treatment, and then impregnated with a silane coupling agent to obtain a pretreated core; Step 3: Coat both sides of the pretreated core with slurry and dry to obtain the core.

3. The method for preparing a high-strength wear-resistant conveyor belt according to claim 2, characterized in that: The silane coupling agent is a mixture of 3-mercaptopropyltrimethoxysilane and 3-aminopropyltriethoxysilane.

4. The method for preparing a high-strength wear-resistant conveyor belt according to claim 3, characterized in that: The mass ratio of 3-mercaptopropyltrimethoxysilane to 3-aminopropyltriethoxysilane is 1:(2-2.5).

5. The method for preparing a high-strength wear-resistant conveyor belt according to claim 2, characterized in that: In step two, the core is subjected to vacuum plasma treatment by introducing a mixture of oxygen and argon gas for 90-100 seconds to obtain the plasma-treated core.

6. The method for preparing a high-strength wear-resistant conveyor belt according to claim 2, characterized in that: In step two, the procedure for impregnation with silane coupling agent is as follows: Take deionized water and ethanol, add glacial acetic acid to adjust the pH to 4.5-5 to obtain a solvent, add 3-mercaptopropyltrimethoxysilane and 3-aminopropyltriethoxysilane, stir for 30-40 minutes to obtain an impregnation solution; immerse the plasma-treated core in the impregnation solution for 20-30 minutes, and dry to obtain the pretreated core.

7. The method for preparing a high-strength wear-resistant conveyor belt according to claim 1, characterized in that: The preparation method of cerium dioxide modified calcium silicate is as follows: take calcium silicate and ethanol, disperse them evenly, add cerium nitrate hexahydrate, stir for 30-40 min, react at 160-165℃ for 12-14 h, filter, wash and dry to obtain cerium dioxide modified calcium silicate.

8. The method for preparing a high-strength wear-resistant conveyor belt according to claim 1, characterized in that: The compound comprises the following components, calculated by weight: 45-50 parts polypropylene, 35-40 parts nitrile rubber, 8-12 parts epoxidized rubber latex, 7-10 parts maleic anhydride-grafted polypropylene, 30-36 parts carbon black, 12-20 parts silica, 1-2 parts bis-[3-(triethoxysilyl)propyl]tetrasulfide, 7-9 parts cerium dioxide-modified calcium silicate, 8-9 parts modified glass fiber, 4-6 parts zinc oxide, 2-3 parts stearic acid, 2-3 parts N-isopropyl-N'-phenyl-p-phenylenediamine, 1-2 parts paraffin wax, 1.5-2 parts sulfur, and 1.5-2 parts N-cyclohexyl-2-benzothiazole sulfenamide.

9. A high-strength wear-resistant conveyor belt prepared by the method for preparing a high-strength wear-resistant conveyor belt according to any one of claims 1-8.